One new species and one new combination of the family Xyalidae (Nematoda: Monhysterida) from the East China Sea - Sun, Yan; Huang, Yong (Zootaxa, 2017)
A new species and a new combination of the family Xyalidae are described from the East China Sea. Elzalia bifurcata sp. nov. is characterized by small body size, relatively long cephalic setae, elongated spicules with bifurcate or y-shaped distal end, simple tubular gubernaculum without apophyses. Elzalia bifurcata sp. nov. differs from the closely related species E. striatitenuis Zhang and Zhang, 2006 and E. mediterranea Vitiello, 1971 by the length of cephalic setae; presence or absence of cervical setae; shape, structure and length of spicules and gubernaculum. Daptonema macrostoma Huang & Xu, 2013 is redescribed and reclassified. The species agrees well with the characters of the genus Paragnomoxyala Jiang & Huang, 2015, such as large buccal cavity; outer labial sensilla papilliform, not setiform; spicules almost straight with slightly curved proximal ends, absence of gubernaculum. Therefore, it is transferred to the genus Paragnomoxyala. As a new combination, the species is named as Paragnomoxyala macrostoma (Huang & Xu, 2013) comb. nov. An emended key to valid species of Elzalia is provided.